A comparative study of three-dimensional printing directions: The degradation and toxicological profile of a PLA/PHA blend. (June 2018) - Gonzalez Ausejo, Jennifer; Rydz, Joanna; Musioł, Marta; Sikorska, Wanda; Sobota, Michał; Włodarczyk, Jakub; Adamus, Grażyna; Janeczek, Henryk; Kwiecień, Iwona; Hercog, Anna; Johnston, Brian; Khan, Habib R.; et al.
Abstract: The use of biobased plastics is of great importance for many applications. Blending thermoplastic polylactide (PLA) with polyhydroxyalkanoate (PHA) enables the formulation of a more mechanically powerful material and this enables tailored biodegradation properties. In this study we demonstrate the 3D printing of a PLA/PHA blend as a potential candidate for biocompatible material applications. The filament for 3D printing consisted of PHA, which contains predominantly 3-hydroxybutyrate units and a small amount of 3-hydroxyvalerate units, as revealed by multistage mass spectrometry (ESI-MS n ). This research found that the properties of 3D printed species before and during abiotic degradation are dependent on printing orientation. Furthermore, the 3D printed specimens exhibited good biocompatibility with HEK293 cells, indicating real promise as biological scaffolds for tissue engineering applications. Highlights: Contact time with printer platform alters the thermal and mechanical properties of materials. Filament arrangement from the algorithm used for printing affects material properties. Processing conditions lead to different degradation profile of the investigated specimens. 3D printed specimens showed good biocompatibility with HEK293 cells.